Pengaruh Implementasi Video Assistant Referee (VAR) Terhadap Keputusan Wasit Dan Asisten Wasit Liga 1 2024-2025 - Nurhadi, Nurhadi; Alkatiri, Thoriq Munir; Hakim, Abdul Aziz; Syamsudar, Bangbang; Widodo, Achmad (Jurnal Kepelatihan Olahraga, 2025)
This study aims to analyze the effect of VAR on decisions taken by referees in League 1 2024-2025. The method used in this study is a quantitative descriptive approach with a correlational research design. The sample in this study was obtained using a total sampling technique consisting of all referees and assistant referees on duty in League 1 with a total of 29 referees and 42 assistant referees on duty in 258 League 1 matches. By examining various variables such as the number of VAR interventions, the types of decisions reviewed. The results of this study indicate that there is a significant influence of the use of VAR on decision making. As many as 85% of decisions that have been given by the referee on the field changed after the referee received intervention from VAR.